ANALYSIS OF FACTORS THAT RELATED MATERNAL SEVERE PREECLAMPSIA TO THE ASPHYXIA OF NEW BORN BABY IN SOEBANDI HOSPITAL JEMBER REGENCY - Ida Srisurani Wiji Astuti (UNEJ e-Proceeding)
An American study (Nawal,M. 2008) saidthat“Approximately 529,000 women die frompregnancy-related causes annually and almost all(99%) of these maternal deaths occur indeveloping nations. One of the United Nations’Millennium Development Goals is to reduce thematernal mortality rate by 75% by 2015. Causes ofmaternal mortality include postpartumhemorrhage, eclampsia, obstructed labor, andsepsis. Many developing nations lack adequatehealth care and family planning, and pregnantwomen have minimal access to skilled labor andemergency care. Basic emergency obstetricinterventions, such as antibiotics, oxytocics,anticonvulsants, manual removal of placenta, andinstrumented vaginal delivery, are vital to improvethe chance of survival.”Nationally, East Java province occupies the top fivethe rising trend in maternal mortality continues tooccur in East Java. There were 487 cases in 2008,535 cases in 2009, 598 cases in 2010 and 627 casesin2011. The area of ‘Tapal Kuda’ contributes thehighest maternal mortality rate, particularlyJember, Banyuwangi, Situbondo, Bondowoso, andLumajang. Based on data from Health Profile ofEast Java Province in 2011, Jember occupied thetop rank of 38 regencies/cities in East Java. 54cases of maternal death illustrate the poor state. Itcan be said that for four consecutive years (2008-2011), Jember Regency had not shifted from thefirst rank (Dinkes Propinsi Jatim, 2012).In 2012, from January 1st until December 31thSoebandi hospital noted that 423 mothers withpreeclampsia which 319 were severe preeclampsia(Adawiyah, 2014).Perinatal outcome assessment could be done byusing Apgar Score (AS). Less value AS which babydetected in the first minute did not endorse theout come in the future. A retrospective researchconcluding that AS in the early five minute stillbeing important predictor for neonatal deaths, butit cannot use to know about long life outcome. Inother data, amount 13.399 the premature baby(less than 26-36 week) revealed neonatal deathshigher ( 315/ 1000) with AS 0-3 in the first minutethan ( 5/1000 ) with AS 5-7 in the early fiveminutes (Brian, M, et al. 2014).Equal to the imunologic theory by Sudhaberata(2001), due to the mother on the first pregnant willbe formed blocking antibodies. In other side, in thefirst pregnant being performed Human LeucocyteAntigen Protein G (HLA) which conducted maternalimunity. This can make mother rejects product ofconception (placenta) or being intoleratedbetween mother and placenta wich can conductpreeclampsia. Beside that, Desfauza (2008)claimed that any relationship significantly betweenquantity of give birth with asphyxia of the newbornbaby. Data showed mother with 1 - >3 times givebirth ( 60,5% asphyxia) more higher risk than 2 – 3times give birth (36,7% asphyxia).Gestational nutritional status very important toreach well being health status for mother andbaby. Women with low body mass index can getnegative effect when labor such as preterm andlow weight body of the baby (Papathakis, 2005).Conversely, the women with over BMI gets morehigh risk in gestational such as abortion, labor withsectio caesare, preeclampsia, trombosis, perinataldeaths, and macrosomia (Yu, 2006).